ANALISIS PENGARUH JUMLAH WISATAWAN MANCANEGARA DAN NUSANTARA TERHADAP PERTUMBUHAN BIRO PERJALANAN WISATA DI BALI - Jonathan, Billy; Kusuma Negara, I Made; Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p04, 2024)
Bali is famous for its natural beauty, rich culture, and comprehensive tourist facilities. The arrival of international and domestic tourists is an important indicator of the tourism industry in Bali. Travel agencies play a crucial role in planning tourists' vacations and supporting the development of the local tourism industry. This research aims to analyze the impact of the number of foreign and domestic tourist arrivals on the growth of travel agencies in Bali. The data analysis technique used to solve the problems in this research is descriptive quantitative analysis with a Secondary Data Analysis (SDA) approach. The data were analyzed using multiple linear regression, t-test, F-test, and determination coefficient with the assistance of SPSS. The number of foreign and domestic tourist arrivals does not simultaneously affect the growth of travel agencies. The statistical test results show that the foreign tourist variable does not have a significant effect on the growth of travel agencies in Bali, with a significance value of 0.169 (> 0.05). On the other hand, the domestic tourist variable has a significant effect on the growth of travel agencies in Bali, with a significance value of 0.041 (< 0.05). The statistical test results also show that the foreign and domestic tourist variables together contribute 17.3% to the growth of travel agencies in Bali, while the remaining 82.7% is influenced by other variables not examined in this research.